The occurrence of Dirofilaria repens in dogs in the southern Transdanubia - Török, Henrietta Kinga; Turgyán, Ágnes; Szentpáli, Fruzsina; Nagy, Gábor; Csivincsik, Ágnes (Acta Agraria Kaposváriensis, 2022)
Dirofilaria repens causes skin worm infection in canid sepcies and humans. This parasite needs mosquitoes as intermediate hosts in their lifecycle. By warming of the global climate, more and more areas become suitable mosquito habitats. Therefore, mosquito transmitted diseases can emerge in new areas. In this study, the authors investigated the dog population of the south Transdanubia, the southernmost part of Hungary to determine the average D. repens prevalence. By Knott’s test and molecular confirmation of infected status, 11.7% prevalence could be detected in 95 domestic dogs. In risk analysis, urban residence and female sex proved to carry high risk of infection. On the other hand, age, breed, hair length showed no impact on infection status. Though all these features seemed important in mosquito biting success, this study could not support the relevance of them.Acknowledgment: This publication was supported by the EFOP-3.6.3-VEKOP-16-2017-00008 „Innovative  scientific  workshops  in  the Hungarian  agricultural higher education”. The project was co-financed by the European Union and the European Social Fund.
Keywords: Dirofilaria repens; kutya; Dél-Dunántúl